Critical Exponents of Gelation and Conductivity in Polyacrylamide Gels Doped by Multiwalled Carbon Nanotubes - Aktas, Demet Kaya; Evingür, Gülşen Akin; Pekcan, Önder (Informa UK Limited, 2010)
Polyacrylamide (PAM) doped by multiwalled carbon nanotube (MWNT) gels were prepared with different amounts of MWNTs varying in the range between 0.1 and 15 wt%. The PAM–MWNT composite gels were characterized by the steady state fluorescence technique (SSF). The alternative electrical conductivity (AC) of PAM–MWNT composite gels was measured by the dielectric spectroscopy technique. Observations around the gel point, tgel for PAM–MWNTs composite gels showed that the gel fraction exponent β obeyed the percolation result. The critical exponent r of AC electrical conductivity for the composite PAM–MWNT gel was also measured and found to be about 2.0, which agrees with a random resistor network. © Koninklijke Brill NV, Leiden, 2010
Keywords: Acrylamide; Hydrogel; Percolation; Multiwalled carbon nanotubes; Fluorescence; Critical phenomena